2019
DOI: 10.1111/jfb.14164
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anticoagulants on stable‐isotope values (δ13C and δ15N) of shark blood components

Abstract: The effects of anticoagulant EDTA and sodium heparin (SH) on stable carbon δ 13 C and nitrogen δ 15 N isotopic values of red blood cells (RBC) and blood plasma in juvenile blacktip reef sharks Carcharhinus melanopterus were analysed. Plasma preserved with anticoagulants was not isotopically distinct from plasma stored in no-additive control tubes but RBC δ 15 N values exhibited small enrichments when preserved with EDTA and SH. Results suggest EDTA and SH are viable anticoagulants for stable isotopic analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Samples were then frozen at −20°C. We assumed that stable isotope value ratios were unaffected by the sodium heparin anticoagulant, based on findings of previous studies (Weideli et al 2019).…”
Section: Study Location and Animal Collectionsmentioning
confidence: 99%
“…Samples were then frozen at −20°C. We assumed that stable isotope value ratios were unaffected by the sodium heparin anticoagulant, based on findings of previous studies (Weideli et al 2019).…”
Section: Study Location and Animal Collectionsmentioning
confidence: 99%
“…Lemons et al (2012) found that whole sea turtle blood samples treated with sodium heparin were significantly enriched in 15 N relative to control samples, though there was a non-significant effect on δ 13 C and δ 15 N values in plasma and red blood cells. In contrast, a study of stable isotopes in shark blood demonstrated that red blood cells treated with sodium heparin were significantly enriched in 15 N relative to control samples (Weideli et al 2019). Bopp et al (2022) found that sodium heparin did not significantly impact δ 34 S values in Atlantic Horseshoe Crab Limulus polyphemus blood.…”
mentioning
confidence: 93%
“…studied, so future studies should be mindful when applying findings to different taxa. If sample volume is not a limiting factor, future studies could consider performing their own analysis to conclude whether adding an anticoagulant affects measurements of δ 13 C, δ 15 N and δ 34 S. We also urge future studies to evaluate the impacts of anticoagulants on the stable isotopes values of plasma and red blood cells as effects may vary across blood components(Lemons et al 2012, Weideli et al 2019.According to Käkelä et al…”
mentioning
confidence: 99%
See 1 more Smart Citation